Data hiding based on noise-like signal addressing - Kuznetsov, A.A.; Smirnov, O.A.; Kiian, A.S.; Kuznetsova, T.Y. (Radiotekhnika, 2020)
There are various computing techniques (methods) to transmit secret messages. For example, cryptographic techniques hide the semantic content of transmitted messages, presenting them in the form of noise-like minor data. Steganographic techniques hide the existence of information messages itself. In this case, messages are hidden inside cover files, i.e., redundant data that are transmitted in an open way and do not cause suspicion in anyone. An outside observer can intercept cover files, analyze and examine them. However, it is very difficult or even impossible to detect and recover hidden data. This article discusses the techniques for hiding data in cover images using direct spread spectrum. We propose a new technique that consists in direct addressing of pseudo-random sequences. On the one hand, it significantly reduces cover file distortion. On the other hand, the error rate in recovered messages does not increase. Our experiments have shown, that Spread Spectrum Steganography technique indeed reduce the distortion in cover images compared to other techniques. We give some illustrative examples and show the advantages of the proposed method. Even with a significant increase in encoding density, the quality of cover images does not degrade. We also conduct experiments and evaluate image quality based on Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR). The obtained results of experimental studies confirm the adequacy and reliability of the research results. The main disadvantage of the proposed data hiding technique is a high computational complexity. To recover messages, it is necessary to calculate sequentially the correlation coefficients with a large number of pseudo-random sequences.